Synthesis of mesoporous silica for adsorption of heavy metal / Elham O.S.J ... [et al.] - Elham, O.S.J; Mohiden, M.A; Jemadi, N.A.I; Sulaiman, M.I (2018)
In this study, synthesis of mesoporous silica was prepared for the adsorption of heavy metal which are Pb and Zn. The silica was prepared using sulfuric acid (H2SO4) and sodium silicate (NaSiO3) by using sol-gel process. The effect of essential parameters on the removal efficiency including initial concentration and contact time were studied. Silica adsorb highest removal efficiency in Pb compared to Zn which was recorded at 88.64% at 50 ppm during 90 minutes. The percentage removal of Zn also increases as the initial concentration increases. The higher the concentration, the higher the percentage removal. The percentage removal of Pb was increased as the contact time increase while the percentage removal of Zn was decreased as the contact time increase. The selectivity of Pb was higher than Zn. This is because Pb was adsorb more on the surface of the adsorbent. Thus, it can be concluded that silica is suitable to be used as an adsorbent in our country because it has structural formula that has the ability to adsorb heavy metal in the wastewater in our country